Burnout among working mothers: The role of work-life balance and perceived organizational support - Bagus Riyono; Gebrina Rezki (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
The pandemic of COVID-19 has influenced business in general. In response to the COVID-19 pandemic, most companies or organizations have been implementing work from home (WFH). For working mothers who have children, this WFH policy creates a more stressful situation since they simultaneously have to deal with work and family in the same place. This study investigated the role of work-life balance and perceived organizational support in the level of burnout tendency among working mothers. Two hundred thirty-seven working mothers who work from home participated in this study. Questionnaires were distributed to the working mothers to measure work-life balance, perceived organizational support, and burnout tendency. Multiple linear regression was used to test the hypothesis. The results show work-life balance and perceived organizational support simultaneously predict burnout tendency. However, perceived organization support, especially a concern for employee welfare, contributes more to reducing burnout. Therefore, human resource management may develop a policy to reduce burnout among women employees by concerning employee welfare in terms of compensation and benefit and creating a conducive working environment